A house for hermit crab eaudiobook - Carle, Eric (Recorded Books Inc., 2015)
Hermit Crab lives in a little shell house on the ocean floor. Wherever he crawls, he carries the shell on his back. He feels safe and snug in his cozy house. But in January, the shell begins to feel tight. Hermit Crab steps out of his safe house into the open sea. Without his shell, the ocean floor seems frightening. Large, hungry fish swim all around. When Hermit Crab finds a bigger, empty shell, he wiggles into it. It feels just right. But it's so plain. Will he ever feel at home in his new house? Popular children's author and illustrator Eric Carle captivates young readers with this delightful tale of a young crab growing up. With the available print and audio book combination, youngsters will enjoy seeing the beauty of Hermit Crab as he changes and the amazing ocean world around him. Narrator John McDonough provides the perfect voice for the young crab as he increases both in size and self-confidence.